2021
DOI: 10.3390/ma14195674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrothermal Time on Structure and Photocatalytic Property of Titanium Dioxide for Degradation of Rhodamine B and Tetracycline Hydrochloride

Abstract: Using butyl titanate and absolute ethanol as raw materials, TiO2 was prepared by a hydrothermal method with different hydrothermal times, and the influences of hydrothermal time on the structure and photocatalytic performance of TiO2 were investigated. The obtained samples were characterized by XRD, SEM, TEM, BET, PL and DRS, separately. The results show that TiO2 forms anatase when the hydrothermal time is 12 h, forms a mixed crystal composed of anatase and rutile when the hydrothermal time is 24 h, and forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 47 publications
2
12
0
Order By: Relevance
“…To determine the active species in photocatalytic reaction process, benzoquinone (BQ), ammonium oxalate (AO) and isopropanol (IPA) were added to capture the active groups, such as ·O 2 − , h + and ·OH, during the TC photodegradation process by Ag@SnO 2 /TiO 2 [ 51 , 52 ]. The results are shown in Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
“…To determine the active species in photocatalytic reaction process, benzoquinone (BQ), ammonium oxalate (AO) and isopropanol (IPA) were added to capture the active groups, such as ·O 2 − , h + and ·OH, during the TC photodegradation process by Ag@SnO 2 /TiO 2 [ 51 , 52 ]. The results are shown in Figure 9 .…”
Section: Resultsmentioning
confidence: 99%
“…The growth process of the nanotube structure from rutile TiO 2 on Ti foil is investigated by the morphology change of TiO 2 films prepared with different hydrothermal durations. TiO 2 with different structures was prepared by a hydrothermal method using butyl titanate and absolute ethanol as raw materials [ 39 ]. Researchers found that anatase TiO 2 is formed when the hydrothermal time is 12 h, TiO 2 forms mixed crystals of anatase and rutile when the hydrothermal time is 24 h, and rutile TiO 2 is formed when the hydrothermal time is 36 h. Their SEM images are shown in Figure 2 F.…”
Section: Tio 2 and Its Composites Materialsmentioning
confidence: 99%
“… ( A ) Steps involved in the sol–gel process to synthesize MONPs [ 20 ]; ( B ) scanning electron microscopy (SEM) ( a ) and transmission- electron microscopy (TEM) ( b ) images of antimicrobials synthesized by the sol–gel method and thermally treated at 350 °C for 2 h [ 25 ]; ( C ) illustration of rGO/TiO 2 nanocomposite formation [ 30 ]; ( D ) SEM images of TiO 2 -Sm ( a ) and TiO 2 -Ag ( b ) [ 31 , 32 ]; ( E ) schematic diagram showing all steps involved in a generic green synthesis mediated by plant extract using the coprecipitation method [ 35 ]; ( F ) SEM images of different TiO 2 samples [ 39 ]; ( G ) illustration of ALD [ 47 ]; ( H ) different PP mesh samples [ 44 ]. …”
Section: Tio 2 and Its Composites Materialsmentioning
confidence: 99%
“…A review from 2021 with the title “Recent progress on Ag/TiO 2 photocatalysts: photocatalytic and bactericidal behaviors” reported more than 500 papers focused on the physicochemical properties of Ag-TiO 2 nanoscale materials [ 11 ]. Several distinct routes have been applied for Ag-TiO 2 synthesis: for instance, sol-gel [ 12 , 13 ], co-precipitation [ 14 ], and hydrothermal methods [ 15 , 16 ], leading to bulk polycrystalline powders, as well as deposition/reduction techniques [ 17 , 18 ], resulting in thin layered films. Each preparation technique has been used to obtain an efficient, stable, and scalable photocatalyst.…”
Section: Introductionmentioning
confidence: 99%